Region-specific difference in apoE4-dependent glial responses to focal brain injury - 이성은 (The Graduate School, Ajou University, 2022)
Apolipoprotein E (apoE) involves in various physiological functions including lipid transports, synaptic plasticity and immune modulation. Epidemiological studies suggest that apoE4 isoform increase the risk of post-traumatic sequelae. To understand the involvement of apoE4 on the clinical heterogeneity of posttraumatic neurodegeneration the region-specific effect of apoE4 was studies. Two focal brain injuries were produced separately into motor cortex and hippocampus within a mouse. ApoE4 (4KI) and apoE3 knock-in (3KI), apoE knock-out, and wildtype mice were used for this study. The diminished injury recovery after focal damage was noted in hippocampus of 4KI mice compared to 3KI mice at recovery stage, which was shown by reduced synaptic protein levels on western blot. Early activations of glial cells and infiltrated monocytes demonstrating increased GFAP, Iba-1 and CD45 intensities on immunohistochemistry were also characteristic to 4KI mice. Interestingly, these apoE4-isoform depending changes were selective to hippocampus, not in motor cortex. Further, inverse correlation of microglial activations with number of neurons on immunohistochemistry and injured volume reduction on follow-up MRI was evident in hippocampus. This study demonstrates the effect of interaction between apoE4 and focal brain damage is specific to hippocampus. And it suggests that the delicate manipulation of inflammatory cell responses in hippocampus could be a strategy to diminish neurodegeneration and post-traumatic cognitive dysfunction in apoE4 carriers.
학위논문(석사)--아주대학교 일반대학원 :의생명과학과,2022. 2
Keywords: Apolipoprotein E; focal brain injury; glial activation; injury repair